A new approach to nonlinear modelling of dynamic systems based on fuzzy rules - Bartczuk, Łukasz; Przybył, Andrzej; Cpałka, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
For many practical weakly nonlinear systems we have their approximated linear model. Its parameters are known or can be determined by one of typical identification procedures. The model obtained using these methods well describes the main features of the system`s dynamics. However, usually it has a low accuracy, which can be a result of the omission of many secondary phenomena in its description. In this paper we propose a new approach to the modelling of weakly nonlinear dynamic systems. In this approach we assume that the model of the weakly nonlinear system is composed of two parts: a linear term and a separate nonlinear correction term.
Keywords: nonlinear modelling; dynamic systems; fuzzy systems; interpretability of fuzzy systems; evolutionary algorithms